To use the point-slope form equation \(y - y_1 = m(x - x_1)\), we can substitute the values from the problem:
- Slope \(m = 2\)
- Point \((x_1, y_1) = (-4, 3)\)
Substituting these into the point-slope form equation:
\[ y - 3 = 2(x - (-4)) \]
This simplifies to:
\[ y - 3 = 2(x + 4) \] \[ y - 3 = 2x + 8 \]
Now, we add 3 to both sides to convert it to slope-intercept form \(y = mx + b\):
\[ y = 2x + 8 + 3 \] \[ y = 2x + 11 \]
So, the equation of the line in slope-intercept form is:
\[ y = 2x + 11 \]
The correct choice from the options provided is:
y = 2x + 11